Tomato plant response to heat stress: a focus on candidate genes for yield-related traits - Graci, Salvatore; Barone, Amalia (Frontiers in Plant Science, 2024)
Climate change and global warming represent the main threats for many agricultural crops. Tomato is one of the most extensively grown and consumed horticultural products and can survive in a wide range of climatic conditions. However, high temperatures negatively affect both vegetative growth and reproductive processes, resulting in losses of yield and fruit quality traits. Researchers have employed different parameters to evaluate the heat stress tolerance, including evaluation of leaf- (stomatal conductance, net photosynthetic rate, Fv/Fm), flower- (inflorescence number, flower number, stigma exertion), pollen-related traits (pollen germination and viability, pollen tube growth) and fruit yield per plant. Moreover, several authors have gone even further, trying to understand the plants molecular response mechanisms to this stress. The present review focused on the tomato molecular response to heat stress during the reproductive stage, since the increase of temperatures above the optimum usually occurs late in the growing tomato season. Reproductive-related traits directly affects the final yield and are regulated by several genes such as transcriptional factors, heat shock proteins, genes related to flower, flowering, pollen and fruit set, and epigenetic mechanisms involving DNA methylation, histone modification, chromatin remodelling and non-coding RNAs. We provided a detailed list of these genes and their function under high temperature conditions in defining the final yield with the aim to summarize the recent findings and pose the attention on candidate genes that could prompt on the selection and constitution of new thermotolerant tomato plant genotypes able to face this abiotic challenge.